Law Enforcement Against Children as Underage Motorcyclists at the South Bolaang Mongondow District Police - Aris mawanti Puputo; Lucyane Djaafar; Nopiana Mozin (SEAN Institute, 2026)
The increasing use of motorcycles among minors is a concerning phenomenon because it is not balanced by legal awareness and traffic safety. This study aims to analyze law enforcement against children as underage motorcyclists and identify the factors that influence it in the Bolaang Mongondow Selatan Regency Police area. The method used is qualitative research with a descriptive approach, through data collection techniques such as interviews, observation, and documentation. The results of the study indicate that law enforcement is carried out through three main approaches: preventive, repressive, and coordinative. The preventive approach is realized through socialization and patrols, the repressive approach through warnings, tickets, and summoning parents, while the coordinative approach through cooperation with schools, parents, and local governments. However, the effectiveness of law enforcement is still influenced by factors such as a suboptimal legal structure, low public awareness, and strong socio-cultural influences that are permissive towards violations. The conclusion of this study confirms that law enforcement has been carried out systematically, but requires strengthening synergy between the authorities, the community, and the social environment to improve legal compliance and traffic safety in a sustainable manner.